2009
DOI: 10.1002/chem.200902180
|View full text |Cite
|
Sign up to set email alerts
|

Metallocyclo‐ and Polyphosphazenes Containing Gold or Silver: Thermolytic Transformation into Nanostructured Materials

Abstract: A cyclotriphosphazene bearing two 4-oxypyridine groups on the same phosphorus atom, gem-[N(3)P(3)(O(2)C(12)H(8))(2)(OC(5)H(4)N-4)(2)] (I), and its analogous polymer [{NP(O(2)C(12)H(8))}(0.7){NP(OC(5)H(4)N-4)(2)}(0.3)](n) (II), have been used to prepare gold or silver, cyclic and polymeric, metallophosphazenes. The following complexes, gem-[N(3)P(3)(O(2)C(12)H(8))(2)(OC(5)H(4)N-4{ML})(2)] (ML=Au(C(6)F(5)) (1) or Au(C(6)F(5))(3) (2)), [N(3)P(3)(O(2)C(12)H(8))(2)(OC(5)H(4)N-4{AuPPh(3)})(2)][NO(3)](2) (3), and [N(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 77 publications
1
31
0
Order By: Relevance
“…This corroborates our previous results that pyrolysis of organometallic derivatives of cyclotriphosphazenes yields metallic nanostructured phosphates or pyrophosphates [19][20][21][22][23][24][25][26]. The results from precursor II also corroborate this hypothesis even if no cyclophosphazenes are present since the phosphine acts as the source of phosphorus atoms.…”
Section: Insights Into the Formation Mechanismsupporting
confidence: 91%
See 3 more Smart Citations
“…This corroborates our previous results that pyrolysis of organometallic derivatives of cyclotriphosphazenes yields metallic nanostructured phosphates or pyrophosphates [19][20][21][22][23][24][25][26]. The results from precursor II also corroborate this hypothesis even if no cyclophosphazenes are present since the phosphine acts as the source of phosphorus atoms.…”
Section: Insights Into the Formation Mechanismsupporting
confidence: 91%
“…These precursors are depicted in Scheme 1 and will be denoted throughout the paper as precursors (I) -(VII). As we previously reported, the use of metallic derivatives of phosphazenes as precursors leads to the formation of phosphorus-containing nanoparticles of phosphates or pyrophosphates [19][20][21][22][23][24][25][26]. With the aim of designing an alternative method to obtain nanostructured materials of metal oxides without using phosphorus, we show that this is possible using precursors I, II, VI and VII (see Scheme 1).…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…By comparison, relatively few solid-state strategies for pure metallic nanostructured materials have been reported [18][19][20][21][22] . In recent work [23][24][25][26][27][28][29] , we reported a new solid-state method allowing the formation of metallic (M), oxidic (M x O y ) and (pyro)phosphate-based (M x P y O z ) nanostructured materials without necessitating liquids or solutions. Detailed investigations have shown that the resulting structures and their shapes strongly depend on the metal used, which can be a noble, transition or valve metal, and also on the molecular precursors to which the metal centers are coordinated.…”
Section: Introductionmentioning
confidence: 99%